O Couto Mixto: Autogoberno, fronteiras e soberanías distantes - López Mira, Álvaro Xosé (Madrygal. Revista de Estudios Gallegos, 2008)
This study is focused on some socio-political issues regarding an organizational entity that dates from 19th century. This organization, now defunct, is located in the Galician-Portuguese raia seca (land border between Galicia and Portugal) called Couto Mixto. We are referring to one potential, perhaps idealized, Galician-Portuguese Andorra —microcosm of the old Gallaecia Kingdom— which was aborted in 1864 by Spanish and Portuguese governments within the framework of a mutual agreement. In recent years, this particular organization has attracted renewed interest because it presents peculiar features which could serve as a model for the innovation of the “tired” European representative democracies of the early 21th century.